1984
DOI: 10.1083/jcb.99.2.686
|View full text |Cite
|
Sign up to set email alerts
|

Inositol incorporation into phosphoinositides in retinal horizontal cells of Xenopus laevis: enhancement by acetylcholine, inhibition by glycine.

Abstract: The absorption of light by photoreceptor cells leads to an increased incorporation of [2-3H]inositol into phosphoinositides of horizontal cells in the retina of Xenopus laevis in vitro. We have identified several retinal neurotransmitters that are involved in regulating this response. Incubation with glycine, the neurotransmitter of an interplexiform cell that has direct synaptic input onto horizontal cells, abolishes the light effect. This inhibition is reversed by preincubation with strychnine. Acetylcholine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In the retina, light stimulation elicits an increased phosphoinositide turnover that is mediated in part by release of ACh (Anderson and Hollyfield, 198 I ;Anderson et al, 1983; Schmidt, 1983a,b) and can be blocked by administration of glycine (Anderson and Hollyfield, 1984). The inhibitory effect of glycine is, in turn, reversed by preincubation with strychnine.…”
Section: Modulation Of Phosphoinositide Turnover By Inhibitory Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the retina, light stimulation elicits an increased phosphoinositide turnover that is mediated in part by release of ACh (Anderson and Hollyfield, 198 I ;Anderson et al, 1983; Schmidt, 1983a,b) and can be blocked by administration of glycine (Anderson and Hollyfield, 1984). The inhibitory effect of glycine is, in turn, reversed by preincubation with strychnine.…”
Section: Modulation Of Phosphoinositide Turnover By Inhibitory Receptorsmentioning
confidence: 99%
“…Thus, although forskolin failed to reduce either carbamoylcholine-or norepinephrine-mediated stimulation of inositol lipid turnover in cerebral cortex slices (Hollingsworth and Daly, 1985), an inhibitory effect was observed by Nicchitta and Williamson (1986), using nerve ending preparations. Similarly, although it has been claimed that administration of excitatory amino acids (kainic acid, NMDA, or DL-homocysteate) exerts an inhibitory effect on phosphoinositide turnover elicited by carbamoylcholine, histamine, or K+ depolarization, and not by norepinephrine (Baudry et al, 1986), an inhibition of norepinephrinelinked, and not of carbamoylcholine-linked, stimulation was observed by Nicoletti et al (1986b).In the retina, light stimulation elicits an increased phosphoinositide turnover that is mediated in part by release of ACh (Anderson and Hollyfield, 198 I ;Anderson et al, 1983; Schmidt, 1983a,b) and can be blocked by administration of glycine (Anderson and Hollyfield, 1984). The inhibitory effect of glycine is, in turn, reversed by preincubation with strychnine.…”
mentioning
confidence: 98%
“…In 1981, Anderson and Hollyfield ( 11 ) reported that light stimulates the incorporation of inositol in the vertebrate retina. Light has also been shown to stimulate the generation of PIs in horizontal cells of the retina ( 12 , 13 ). Subsequent studies showed that light adaptation of bovine retinas in situ stimulates PI synthesis in retinal rod outer segment (ROS) membranes in vitro ( 5 ).…”
Section: Phosphoinositides In the Retinamentioning
confidence: 99%
“…Subsequent studies showed that light adaptation of bovine retinas in situ stimulates PI synthesis in retinal rod outer segment (ROS) membranes in vitro ( 5 ). The work described in 1983 and 1984 by Anderson and colleagues revealed a functional significance in photoreceptor horizontal cell synapses ( 12 , 13 ). Light stimulates the PI metabolism in these cells, and these PIPs are important for synaptic ribbon formation, glutamate release, and signaling ( 12 , 13 ).…”
Section: Phosphoinositides In the Retinamentioning
confidence: 99%
See 1 more Smart Citation